Experiences of women living with fibromyalgia: an exploratory study of their information needs and preferences (Rheumatology Reports, 2011)
Women living with fibromyalgia consistently report experiencing a change in their lives in terms of stigma, inability to work, isolation from society and difficulty in managing their illness. Lack of understanding and knowledge about their disease has been linked to compromised health and quality of life. The aim of this study was to explore the experiences of information use of women living with fibromyalgia. A descriptive phenomenology was used for this study. Participants were identified through gatekeepers for women living with fibromyalgia across Canada. Data was collected via taperecorded interviews. The study was conducted in Canada between 2009-2010. Ten women (18 or older) participated in the research. Three essential themes emerged from the analysis that were vital to understand the unique experiences of women: i) understanding the need for information required to live with fibromyalgia, ii) struggling to meet vital and fundamental information needs and iii) transforming themselves to improve health and quality of life. Women living with fibromyalgia have vital and specific information needs and struggle to find and access appropriate information. They use diverse strategies in overcoming some of the challenges in accessing information. Most significantly, women draw on the information to make changes and to begin to coordinate their lives to live with fibromyalgia. For women living with fibromyalgia, the phenomenon of information use has a significant effect on their lives. Healthcare providers are perceived as an important source of information and need to be better informed, more prepared and dedicated to assisting women with their information needs.